Contract delay: what is it and how are we performing? (Construction Economics and Building, 2012)
AbstractThis paper examines the management of contract delays in the construction industry as currently practised, and suggests some best practice alternative methods.Research results about the level of contractor’s time management skills were analysed to determine the related impact on their ability to manage contract delays. A comparison was made between three conditions of contracts used in New Zealand to determine how delay management should be managed with a discussion about how the different contract conditions distribute risk among the parties. Recommendations were made to improve contract conditions, up-skill industry practitioners and ensure student graduates have adequate delay management skills.